Answer:
the radius is something in math
Answer:
It is vertically stretched by a factor of 200 and shifted 10 units up.
Step-by-step explanation:
cool like that
Answer: ![12m^2+19m-18](https://tex.z-dn.net/?f=12m%5E2%2B19m-18)
Step-by-step explanation:
Given
Speed of boat ![v=3m-2\ \text{knots per hour}](https://tex.z-dn.net/?f=v%3D3m-2%5C%20%5Ctext%7Bknots%20per%20hour%7D)
![\text{time t= }4m+9\ \text{hours}](https://tex.z-dn.net/?f=%5Ctext%7Btime%20t%3D%20%7D4m%2B9%5C%20%5Ctext%7Bhours%7D)
![\Rightarrow \text{Distance =speed}\times \text{time}](https://tex.z-dn.net/?f=%5CRightarrow%20%5Ctext%7BDistance%20%3Dspeed%7D%5Ctimes%20%5Ctext%7Btime%7D)
![\Rightarrow \text{Distance d=}(3m-2)\cdot (4m+9)\\\Rightarrow d=12m^2+19m-18](https://tex.z-dn.net/?f=%5CRightarrow%20%5Ctext%7BDistance%20d%3D%7D%283m-2%29%5Ccdot%20%284m%2B9%29%5C%5C%5CRightarrow%20d%3D12m%5E2%2B19m-18)
Answer:
see in the graph, the circle has: the centre I(3; -2)
r = 3
=> the equation: (x - 3)² + (y + 2)² = 9
Answer:
step 2
Step-by-step explanation:
The student first made an error in the step 2.
Because if we simplify the equation A in step 1, we should distribute the right side of the equation following the rule a(b-c) = a*b +a*(-c)
So, it would be
–7y = (-7)*(16)+(-7)*(-2z)
=> -7y = -112 + 14z